2011
DOI: 10.17221/201/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective effect of polydextrose on chicken surimi

Abstract: Kovačević D., Mastanjević K., Kordić J. (2011): Cryoprotective effect of polydextrose on chicken surimi. Czech J. Food Sci., 29: 226-231.Two thermal analysis techniques -Differential scanning calorimetry (DSC) and Differential thermal analysis (DTA), -were used to study the cryoprotective effects of polydextrose on chicken surimi. The samples of chicken surimi were mixed with: (a) different mass fractions of polydextrose (w = 2-10%), (b) κ-carrageenan (w = 0.5%) and different mass fractions of polydextrose (w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is important to note that a synergistic increase of g was reported by Harnkarnsujarit et al [39] On the other hand, the optimization and selection of cryoprotectants in food formulations are a challenging task because the choice of cryoprotectants is based largely on criteria such as low cost, availability, pleasant or acceptable sensory characteristics in foods, and trial-and-error processes and experience of the food manufacturers [15,16,40]. For instance, sucrose and sorbitol concentrations of 4-8% [15,40], polydextrose concentrations of 1-10% [41,42], glucose concentrations of 5-15% [43], maltodextrin concentrations of 5-35% [36,[44][45][46], and maltodextrin-sugars concentrations of 20% (glucose, fructose, and sucrose) [47] have been used as cryoprotectant additives. In some cases, it has been reported that low levels of sugars and sorbitol impart a sweet taste to the products [40,41,43].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that a synergistic increase of g was reported by Harnkarnsujarit et al [39] On the other hand, the optimization and selection of cryoprotectants in food formulations are a challenging task because the choice of cryoprotectants is based largely on criteria such as low cost, availability, pleasant or acceptable sensory characteristics in foods, and trial-and-error processes and experience of the food manufacturers [15,16,40]. For instance, sucrose and sorbitol concentrations of 4-8% [15,40], polydextrose concentrations of 1-10% [41,42], glucose concentrations of 5-15% [43], maltodextrin concentrations of 5-35% [36,[44][45][46], and maltodextrin-sugars concentrations of 20% (glucose, fructose, and sucrose) [47] have been used as cryoprotectant additives. In some cases, it has been reported that low levels of sugars and sorbitol impart a sweet taste to the products [40,41,43].…”
Section: Introductionmentioning
confidence: 99%
“…At present, DSC is one of the most frequently applied techniques in the analysis of the thermal stability of biological systems such as e.g. meat (Tomaszewska-Gras & Konieczny 2010; Kovačević et al 2011). A particular advantage of this technique is related to the potential to analyse proteins in the natural state, without the need to dissolve or extract proteins.…”
mentioning
confidence: 99%